THE USE OF THE HYPNOTIC PHENOMENON TO REMODEL THE SYMPTOM: TWO CASES - Lawrence Bernardes Santana, Victor (Health and Society, 2023)
The hypnotic phenomenon can be a great tool for therapeutic change. With the exception of Milton Erickson, hypnotherapists have yet to fully exploit this potential. Hypnotic language and hypnotic phenomena build a path of change capable of leading the patient to significant accomplishments. The purpose of this article is to present two clinical cases where hypnosis was used in this way and to minimally explain how it was done (Erickson, et al., 1977).